Hepatitis B Seroprotection and the Response to a Challenging Dose among Vaccinated Children in Red Sea Governorate - Sami, Samia M. (Open Access Maced J Med Sci, 2016)
AIM: To assess the long-term effectiveness of hepatitis B virus vaccine and the need for a booster dose among children who received three doses of vaccine during infancy in Red Sea Governorate. METHODS: A cross-sectional study was performed. Interviews with children (9 months to 16 years) and parents were done. Blood samples to assess Hepatitis B markers were tested. Children showing no seroprotection received a booster dose to assess their anamnestic response after four weeks and one year later. RESULTS: None of the participants had evidence of chronic Hepatitis B. The seroprotection rate was 23.3% and it significantly decreased with age. Multivariate logistic analysis revealed that older age was the significant predicting variable for having no seroprotective level, while baseline anti-HBs level < 3.3 IU/L was the predicting variable for not developing early anamnestic response or loss of late anamnestic response. CONCLUSION: Long-term immunity persists among children who received complete series of hepatitis B vaccination during infancy even in absence or reduction of anti-HBs over time. Therefore, a booster dose is not necessary to maintain immunity till the age of sixteen.